Time-varying credibility, anchoring and the Fed's inflation target - Max Diegel (Freie Universität Berlin, School of Business & Economics, 2022)
This paper analyzes the time-varying credibility of the Fed's inflation target in an empirical macro model with asymmetric information, where the public has to learn about the actual inflation target from the Fed's interest rate policy. To capture the evolving communication strategy of the Fed, I allow the learning rule and the structural shock variances to change across monetary policy regimes. I find that imperfect credibility is pronounced during the Volcker Disinflation and to a lesser extend in the aftermath of the 2008 Financial Crisis. The announcement of the 2% target in 2012 did not affect the learning rule strongly but reduced the variance of transitory monetary policy shocks. The results caution against equating long-term inflation expectations of professionals with the perceived inflation target.
urn:nbn:de:kobv:188-refubium-37255-6
Keywords: C11; C32; D83; D82; E31; E52; 330; signal extraction problem; credibility; inflation target; unobserved components; VAR